Seven testaments of world religion and the Zoroastrian older testament - Brown, Brian A. (Rowman & Littlefield, 2020)
Introduces the Avesta scriptures of Zoroastrianism, plus the creation stories from seven other religions and seven apocalypses, showing them all to be derivatively based on Vedic-Zoroastrian originals